Neuroprotective Effect of 3′,4′-Dihydroxyphenylglycol in Type-1-like Diabetic Rats—Influence of the Hydroxytyrosol/3′,4′-dihydroxyphenylglycol Ratio - Rodríguez-Pérez, María Dolores; Pérez de Algaba Fuentes, Inmaculada; Martín Aurioles, Esther; Ortega-Hombrados, Laura; Verdugo, Cristina; Fernández-Prior, María África; Bermúdez-Oria, Alejandra; De-la-Cruz-Cortés, José Pedro; González-Correa, José Antonio (IOAP-MPDI, 2022)
The aim of this study was to assess the possible neuroprotective effect of 3′,4′-dihydroxyphenylglycol (DHPG), a polyphenol from extra virgin olive oil (EVOO), in an experimental model of diabetes and whether this effect is modified by the presence of another EVOO polyphenol, hydroxytyrosol (HT). The neuroprotective effect was assessed in a hypoxia–reoxygenation model in brain slices and by quantifying retinal nerve cells. The animals were distributed as follows: (1) normoglycemic rats (NDR), (2) diabetic rats (DR), (3) DR treated with HT (5 mg/kg/day p.o.), (4) DR treated with DHPG (0.5 mg/kg/day), or (5) with 1 mg/kg/day, (6) DR treated with HT plus DHPG 0.5 mg/kg/day, or (7) HT plus 1 mg/kg/day p.o. DHPG. Diabetic animals presented higher levels of oxidative stress variables and lower numbers of neuronal cells in retinal tissue. The administration of DHPG or HT reduced most of the oxidative stress variables and brain lactate dehydrogenase efflux (LDH) as an indirect index of cellular death and also reduced the loss of retinal cells. The association of DHPG+HT in the same proportions, as found in EVOO, improved the neuroprotective and antioxidant effects of both polyphenols.
Keywords: Diabetes; Hydroxytyrosol; 30 ,40 -dihydroxyphenylglycol; Extra virgin olive oil; diabetic neuropathy; Diabetes mellitus